Fixed search patterns and VLSI architecture for the efficient computation of the versatile video coding fractional motion estimation - Rodrigues Filho, Vanio (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2022.